An improved teaching-learning-based optimization: briefly survey - et. al., Ebtehal Akeel Hamed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Teaching-learning-based optimization algorithm (TLBO) considers a newly advanced heuristic algorithm that depends on the physical appearance of the teaching-learning procedure. Its goal at the reduction of facilely come down into local optimum when working on complicated optimization difficulties that have high dimensional, in this paper, we will review a viewpoint many studies that involved an improved or enhanced teaching-learning-based optimization, that interested by improved learner phase which included the population to avert the potential about overthrowing toward a local optimum. Also, strategies based on the Gaussian perturbation ban the TLBO algorithm from falling within local minima. In this paper also presented the role of an Improved Teaching-learning-based Optimization Algorithm to Determine Job Shop Scheduling issues.